2002
DOI: 10.3390/i3090992
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of Stress Genes and Cytotoxicity in Human Liver Carcinoma (HepG2) Cells Exposed to Pentachlorophenol

Abstract: Pentachlorophenol (PCP) is a biocidal chemical with several industrial, agricultural, and domestic applications. There is accumulating evidence indicating that PCP is highly toxic to humans, with major target organs including the lung, liver, kidneys, heart, and brain. Little is known regarding the molecular basis by which PCP induces toxicity, mutagenesis, and carcinogenesis. Therefore, this research was designed to assess the cellular and molecular responses of HepG 2 cells following exposure to PCP. The cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 39 publications
(40 reference statements)
5
23
0
Order By: Relevance
“…We have previously reported that the overexpression of the HSP70 gene protein is a dose-dependent event in HepG 2 cells exposed to PCP [18, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that the overexpression of the HSP70 gene protein is a dose-dependent event in HepG 2 cells exposed to PCP [18, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations in our laboratory have shown that PCP induces acute toxicity and transcriptionally activates a constellation of stress genes in HepG 2 cells [24]. From our laboratory findings, we demonstrated that PCP has the ability to undergo Phase I biotransformation in the liver (CYP1A1 and XRE), to cause cell proliferation (c-fos), to cause growth arrest and DNA damage (GADD153 and p53), to influence the toxicokinetics of metal ions (HMTIIA), and to induce proteotoxic effects (HSP70 and GRP78) in HepG 2 cells [1,24]. Our laboratory has recently reported that PCP exerts both cytotoxic and mitogenic effects in human liver carcinoma (HepG 2 ) cells [1], and primary culture of catfish hepatocytes [2].…”
Section: Introductionmentioning
confidence: 93%
“…It is believed that the mechanism by which PCP exerts its toxic action involves uncoupling mitochondrial oxidative phosphorylation, thereby causing accelerated aerobic metabolism and increasing heat production [22,23]. Previous investigations in our laboratory have shown that PCP induces acute toxicity and transcriptionally activates a constellation of stress genes in HepG 2 cells [24]. From our laboratory findings, we demonstrated that PCP has the ability to undergo Phase I biotransformation in the liver (CYP1A1 and XRE), to cause cell proliferation (c-fos), to cause growth arrest and DNA damage (GADD153 and p53), to influence the toxicokinetics of metal ions (HMTIIA), and to induce proteotoxic effects (HSP70 and GRP78) in HepG 2 cells [1,24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that chlorinated organic compounds interact with retinoic acid (RA) receptors (Inoue et al, 2010); a possible explanation may be that NaPCP modifies natural ligand signalling in the RA pathway, similar to the effects of PCP on retinoic acid response elements (Dorsey et al, 2002). RA is essential for various developmental processes since it acts on certain genes (e.g.…”
Section: Factormentioning
confidence: 99%